2015
DOI: 10.1007/s00395-014-0458-1
|View full text |Cite
|
Sign up to set email alerts
|

Gene delivery of suppressors of cytokine signaling (SOCS) inhibits inflammation and atherosclerosis development in mice

Abstract: Chronic activation of Janus kinase/signal transducers and activators of transcription (JAK/STAT) pathway contributes to vascular inflammation and atherosclerosis by inducing expression of genes involved in cell proliferation, differentiation and migration. We aimed to investigate whether enforced expression of negative regulators, the suppressors of cytokine signaling (SOCS1 and SOCS3), inhibits harmful JAK/STAT-mediated responses and affects atherosclerosis in apolipoprotein E knockout mice. Adenovirus-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 36 publications
3
38
0
Order By: Relevance
“…JAK/STAT is also a key inflammatory mechanism by which hyperglycemia contributes to the diabetic complications1820. Targeting JAK/STAT activation inhibits proinflammatory genes expression, leukocyte infiltration, and vascular cell activation, thereby preventing development and progression of atherosclerosis in diabetic mice2041. The inflammatory response induced by JAK/STAT pathway comprises different genes including chemokines, cytokines, enzymes and vasoactive proteins, many of them upregulated by diabetic conditions19.…”
Section: Discussionmentioning
confidence: 99%
“…JAK/STAT is also a key inflammatory mechanism by which hyperglycemia contributes to the diabetic complications1820. Targeting JAK/STAT activation inhibits proinflammatory genes expression, leukocyte infiltration, and vascular cell activation, thereby preventing development and progression of atherosclerosis in diabetic mice2041. The inflammatory response induced by JAK/STAT pathway comprises different genes including chemokines, cytokines, enzymes and vasoactive proteins, many of them upregulated by diabetic conditions19.…”
Section: Discussionmentioning
confidence: 99%
“…Altering the SOCS1/SOCS3 balance or the activity of these negative regulators would be an attractive therapeutic approach and is under investigation (96). A therapeutic SOCS1 KIR mimetic peptide has shown great promise in preventing the development of multiple sclerosis in a mouse experimental autoimmune encephalomyelitis model and even ameliorates clinical symptoms of lupus in a rodent model (97).…”
Section: Socs1 Regulates Il-4-induced Irs-2 Signaling In Human Monocytesmentioning
confidence: 99%
“…Previous studies have shown that SOCS1 and SOCS3 are closely correlated with atherosclerosis progression151617. However, they appear to have different expression patterns and play opposing roles during atherogenesis173233.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid excessive inflammation in vivo , some protein inhibitors, such as suppressor of cytokine signalling (SOCS), protein inhibitor of activated STAT (PIAS) and protein tyrosine phosphatases, are involved in negatively regulating JAK/STAT signalling activation14. The findings of previous studies indicate that SOCS1 and SOCS3 are closely correlated with atherosclerosis progression151617. High SOCS1 and SOCS3 expression levels were detected in VSMCs and macrophages in both human atherosclerotic plaques and apolipoprotein E knockout (ApoE −/− ) mouse aortic lesions.…”
mentioning
confidence: 99%